Evaluating Green Communities: Top Eleven Questions to Ask - Mark E. Hostetler (EDIS, 2006)
Circular 1491, a 15-page illustrated article by Mark Hostetler, coaches home buyers in how to find a house with good indoor air quality, that doesn't cost a fortune to heat and cool, is efficient in use of water, and in a nature-friendly neighborhood. Published by the UF Department of Wildlife Ecology and Conservation, June 2006.